Interventions for American cutaneous and mucocutaneous leishmaniasis: a systematic review update. - Ludovic Reveiz; Ana Nilce Silveira Maia-Elkhoury; Rubén Santiago Nicholls; Gustavo Adolfo Sierra Romero; Zaida E Yadon (PLoS ONE)
Introduction Leishmaniasis is an important public health problem in the Americas. A Cochrane review published in 2009 analyzed 38 randomized controlled trials (RCT). We conducted a systematic review to evaluate the effects of therapeutic interventions for American cutaneous and mucocutaneous leishmaniasis. Methods All studies were extracted from PubMed, Embase, Lilacs (2009 to July, 2012 respectively), the Cochrane Central Register of Controlled Trials (6-2012) and references of identified publications. RCTs' risk of bias was assessed. Results We identified 1865 references of interest; we finally included 10 new RCTs. The risk of bias scored low or unclear for most domains. Miltefosine was not significantly different from meglumine antimoniate in the complete cure rate at 6 months (4 RCT; 584 participants; ITT; RR: 1.12; 95%CI: 0.85 to 1.47; I2 78%). However a significant difference in the rate of complete cure favoring miltefosine at 6 months was found in L. panamensis and L. guyanensis (2 RCTs, 206 participants; ITT; RR: 1.22; 95%CI: 1.02 to 1.46; I2 0%). One RCT found that meglumine antimoniate was superior to pentamidine in the rate of complete cure for L. braziliensis (80 participants, ITT; RR: 2.21; 95%CI: 1.41 to 3.49), while another RCT assessing L. guyanensis did not find any significant difference. Although meta-analysis of three studies found a significant difference in the rate of complete cure at 3 months favoring imiquimod versus placebo (134 participants; ITT; RR: 1.45; 95%CI: 1.12 to 1.88; I2 0%), no significant differences were found at 6 and 12 months. Thermotherapy and nitric oxide were not superior to meglumine antimoniate. Conclusion Therapeutic interventions for American cutaneous and mucocutaneous leishmaniasis are varied and should be decided according to the context. Since mucosal disease is the more neglected form of leishmaniasis a multicentric trial should be urgently considered.